Tantangan Dan Solusi Dalam Implementasi Kebijakan Pendidikan Anak Usia Dini Di Kabupaten Tuban - Satunggale Kurniawan; Ahmad Zainul Ihsan Arif (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
This study aims to identify key challenges and formulate strategic solutions for implementing Early Childhood Education (ECE) policy in Tuban Regency, East Java. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis involving PAUD institutions, stakeholders, and local communities. The findings reveal several significant challenges, including inadequate infrastructure, low qualifications and competencies of educators, limited budget allocations, and low community awareness and participation. Discrepancies between national policies and regional readiness further hinder effective policy implementation. Nevertheless, initiatives such as teacher training, the development of Holistic Integrative PAUD, and institutional mentoring have shown promising potential. This study recommends strengthening cross-sectoral collaboration, providing continuous training programs, ensuring equitable funding, and conducting massive public awareness campaigns. The results underline the importance of adaptive and participatory approaches in the successful implementation of locally contextualized PAUD policies. These findings are expected to contribute to more effective and sustainable policy formulation for inclusive and quality early childhood education development in local regions.